Tea bioactive components prevent carcinogenesis via anti‐pathogen, anti‐inflammation, and cell survival pathways. Issue 2 (29th January 2021) - Fan, Xiangqi; Xiao, Xiangjun; Mao, Xiangbing; Chen, Daiwen; Yu, Bing; Wang, Jianping; Yan, Hui
Abstract: Cancer seriously impairs human health and survival. Many perturbations, such as increased oxidative stress, pathogen infection, and inflammation, promote the accumulation of DNA mutations, and ultimately lead to carcinogenesis. Tea is one of the most highly consumed beverages worldwide and has been linked to improvements in human health. Tea contains many active components, including tea polyphenols, tea polysaccharides, L ‐theanine, tea pigments, and caffeine among other common components. Several studies have identified components in tea that can directly or indirectly reduce carcinogenesis with some being used in a clinical setting. Many previous studies, in vitro and in vivo, have focused on the mechanisms that functional components of tea utilized to protect against cancer. One particular mechanism that has been well described is an improvement in antioxidant capacity seen with tea consumption. However, other mechanisms, including anti‐pathogen, anti‐inflammation and alterations in cell survival pathways, are also involved. The current review focuses on these anti‐cancer mechanisms. This will be beneficial for clinical utilization of tea components in preventing and treating cancer in the future.